To trade or not to trade: non-separable farm household models in partial and general equilibrium. - Lofgren, Hans; Robinson, Sherman (International Food Policy Research Institute, 1999)
Empirical evidence and microeconomic theory suggest that, in many settings, farm household production and consumption decisions are non-separable. Non-separability may have important policy implications, including lack of response or threshold effects when incentives change. This paper extends the literature in two ways. First, we develop a non-separable farm household model with transaction costs and endogenous choice of market "regime" (surplus, self-sufficiency, or deficit) for production-consumption items (commodities and factors that are both demanded and supplied by the household). Second, we embed this household model in an economywidecomputable general equilibrium model which is formulated as a mixed-complementarity problem. Simulations with a model based on data for a stylized, low-income, Sub-Saharan African country show that the proposed formulation enhances our ability to analyze the impact of exogenous changes on African farmers."